EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI PADI CIGELUIS DI SUBAK ANYAR SIDEMBUNUT KECAMATAN BANGLI KABUPATEN BANGLI - Sukerta, I Kadek Agus; Kardi, Cening; Yudiarini, Nyoman (Fakultas Pertanian Universitas Mahasaraswati Denpasar, 2018)
The purpose of this research is to know: (1) the influence of rice seed production factor, phonska fertilizer, organic fertilizer, urea fertilizer, and labor to cigeluis paddy farm production in Subak Anyar Sidembunut Bangli District Bangli, and (2) Efficiency of farm production factor usage Cigeluis rice in Subak Anyar Sidembunut Bangli District of Bangli.        This research is a survey research conducted in Subak Anyar Sidembunut Bangli District of Bangli District. This location is found by simple random sampling, while the determination of respondents using census method. The production function of this research is the production function of